2015
DOI: 10.26719/2015.21.8.591
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of rabies in Oman: a retrospective study (1991–2013)

Abstract: Animal bites and rabies are under-reported in many developing countries and there is poor understanding of the disease burden. The aim of this study was to map the epidemiology of animal bites and rabies in Oman over the period 1991-2013. In a cross-sectional, descriptive, surveillance-based study, all data about animal bites and rabies from the national communicable disease surveillance system were analysed. A total of 22 788 cases of animal bites were reported. Most bites were to males (70%) and the 10-19 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 6 publications
3
30
0
Order By: Relevance
“…There were more male cases than female, 55.5% and 44.5%, respectively. Comparable reports were from Oman, 70% male cases, and 26% of 10-19 age group (Abaidani et al, 2015), 62.8% male cases and 38.5% of cases were children in Ethiopia (Yibrah and Damtie, 2015). Teklu et al from Ethiopia was reported more male cases (63%) and children (63%) (Teklu et al, 2017).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…There were more male cases than female, 55.5% and 44.5%, respectively. Comparable reports were from Oman, 70% male cases, and 26% of 10-19 age group (Abaidani et al, 2015), 62.8% male cases and 38.5% of cases were children in Ethiopia (Yibrah and Damtie, 2015). Teklu et al from Ethiopia was reported more male cases (63%) and children (63%) (Teklu et al, 2017).…”
Section: Discussionmentioning
confidence: 86%
“…Among animal species responsible for the bites 98% was due to dog, while the remaining were cat, fox and donkey. Different report was from Oman where most common bites from cats (Abaidani et al, 2015). This difference may be due to cultural and religion differences to keep dog as pet animal.…”
Section: Discussionmentioning
confidence: 92%
“…The country was thought to be rabies-free until 1990. The first human case of rabies was reported in 1990 from a young schoolboy who was bitten by a fox [ 17 ]. From then onwards, the disease spread across the country.…”
Section: Resultsmentioning
confidence: 99%
“…A phylogenetic analysis of samples collected during 2014 showed that all rabies viruses were related to each and that foxes were the main reservoir in the country [ 18 ]. The number of animal rabies cases is roughly similar across the governorates and the highest percentages of animal bites to humans were from cats (48.3%), dogs (35.2%), foxes (5.2%), and a few other animals [ 17 ]. In Oman, it is probably most advisable to focus on the vaccination of wildlife first before tackling vaccination of domestic animals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation